LANDSLIDE RISK ZONING THROUGH REMOTE REMOTE SENSING AND GIS - KAMARUDIN, MUHAMMAD HAZWAN (Universiti Teknologi Petronas, 2008)
The purpose of this study is to classifY relevant information from satellite image to be used in landslide risk zoning. The information needed consists of the types of land use at the study area such as arable land, dense forest, rocky area, agriculture, mixed cultivated and grassland. All the relevant information that are contributing to the landslide was extracted from the satellite image using the MultiSpec W32 software. The study area took placed at a certain area of Cameron Highlands which was located in Pahang, Malaysia. The types of land use extracted from the satellite image using image processing software and the steepness of the slopes determined using Arc view GIS 3.3 software later on were grouped base on the possibility for landslide to occur. The outcome ofthis study is expected to be able to assist the users to identifY the area which are prone to landslide just by looking atthe satellite image and land use.